NEWLY-PACKAGED BALI TOURIST PERFORMING ARTS IN THE PERSPECTIVE OF CULTURAL STUDIES - Ruastiti, Ni Made; Parimartha, I Gde; Sedyawati, Edi; Suastika, I Made (E-Journal of Cultural Studies, 2009)
This research is focused on the newly packaged tourist performing arts; they are anew concept and seem to be different from the general tourist performing arts. They arepackaged from various components of Balinese arts and managed as large scale-touristperforming arts in terms of materials, space, and time of their performances. The researchercalls them new types of Bali tourist performing arts because how they are presented isnew and different from the traditional tourist performing arts which are simply performed.In this research, the newly-packaged performing arts are analyzed in the perspective ofcultural studies.The research was carried out at three palaces in Bali; they are Mengwi Palace inBadung regency, Anyar Palace at Kerambitan, Tabanan regency, and Banyuning Palace atBongkasa, Badung regency. There are three main problems to be discussed: firstly, how dothe tourist performing arts emerge in all the palaces? Secondly, are they related to thetourist industry developed in the palaces?, thirdly, what is the impact and meaning of themfor the sake of the palaces, society, and Balinese culture? The researcher uses a qualitativemethod and an interdisciplinary approach as characteristics of cultural studies. The theoriesused are hegemony, deconstruction, and structuration.The result shows that the tourism development at all the palaces has made the localsociety become more critical. The money-oriented economy based on the spirit of gettingbenefit has made the emergence of comodification in all sectors of life. The emergence oftourist industry at the palaces has led to the idea of showing all of the useful art and culturalpotentials which at the palaces and their surroundings. Theoretically, the palaces can bestated to have deconstructed the concept of presenting the Bali tourist performing arts into anew one, that is, “the newly packaged Bali tourist performing arts”.It has been observed that all the palaces have developed t “Newly packaged Balitourist Performing Arts” but they are different in themes. At Mengwi Palace the theme is‘procession of religious rituals’, at Anyar Palace, Kerambitan, the theme is “ritualprocession of welcoming the kingdom’s guests” and at Banyuning Palace, Bongkasa, thetheme is “ritual procession of wedding”. The differences can be seen in the componentspresented in the performances.